Creación y gestión de contenidos para redes sociales, como herramienta de marketing digital para la Asociación de Emprendedores de Chimborazo - Lara Samaniego, Hugo Marcelo (2023)
Nowadays, associations and companies have seen the need to incorporate content creation and management as strategies in digital media, such as social networks. This is for its scope to achieve better marketing and thus stop handling it traditionally, using ATL or conventional advertising, to reach wide audiences. These have lost ground, thanks to digital media, since social networks allow for greater marketing reach and more interaction with audiences because digital marketing allows you to use strategies, such as Inbound Marketing, to meet the needs of audiences defined through a buyer person. From the results obtained, the advantages and disadvantages of the Association were taken into account in the management of social networks and digital marketing as the strategy of Inbound Marketing to design a proposal according to the environment that adapts to the needs of each of the entrepreneurs that make up the Association. Being a guide to the references when creating content and handling Digital Marketing.